Association between anatomic variations of extrahepatic and intrahepatic bile ducts: Do look up!. Issue 4 (20th January 2023) - Renzulli, Matteo; Brandi, Nicolò; Brocchi, Stefano; Balacchi, Caterina; Lanza, Carolina; Pettinari, Irene; Stefanini, Bernardo; Carrafiello, Giampaolo; Piscaglia, Fabio; Golfieri, Rita; Marasco, Giovanni
Abstract: Biliary anatomic variations are usually asymptomatic, but they may cause problems in diagnostic investigations and interventional and surgical procedures, increasing both their technical difficulty and their postoperative complication rates. The aim of the present study was to evaluate the prevalence of anatomic variations in the intrahepatic biliary ducts (IHBD) in relation to demographical and clinical characteristics in a large study population requiring magnetic resonance cholangiopancreatography (MRCP) for various clinical conditions. The possible association between IHBD and extrahepatic biliary ducts (EHBD) variants was then explored. From January 2017 to May 2019, 1004 patients underwent MRCP. Demographical and clinical data were collected. IHBD and EHBD anatomy were recorded and the EHBD anatomy was classified using both qualitative and quantitative classifications. The presence of a type 3 EHBD variant (an abnormal proximal cystic duct [CD] insertion) in both qualitative and quantitative classifications and an intrapancreatic CD were associated with the presence of IHBD variants at univariate analysis ( p  = 0.008, p  = 0.019, and p  = 0.001, respectively). The presence of a posterior or medial insertion of the CD into the EHBD was a strong predictive factor of the presence of IHBD variants both at uni‐ and multivariate analysis ( p  = 0.002 and p  = 0.003 for posterior insertion and p  = 0.002 and p  = 0.002 for medial insertion, respectively). The presence of gallstones on MRCP resulted in a strong predictor of the presence of an anatomical variant of the IHBD both at uni‐ and multivariate analysis ( p  = 0.027 and p  = 0.046, respectively). In conclusion, the presence of a type 3 variant of the EHBD, an intrapancreatic CD and, especially, a posterior/medial CD insertion into the EHBD represent predictive factors of the concomitant presence of IHBD variants, thus radiologists must be vigilant when encountering these EHBD configurations and always remember to "look up" at the IHBD. Finally, the presence of an IHBD variant is a strong predictive factor of gallstones. Abstract : The presence of the Type 3 variant of extrahepatic bile duct [i.e. an abnormal proximal CD insertion, according to both the standard classification (CDDP/EHBD ratio > 66%) and the new classification (CDDP/EHBD ratio >75%)], an intrapancreatic CD (i.e. an abnormal low CD insertion) and, especially, a posterior or medial insertion of the CD into the EHBD represent predictive factor for the concomitant presence of IHBD variants, thus radiologists must be vigilant when encountering these anatomical configurations and always remember to "look up" also in the intrahepatic system.